(untitled) (International Journal of Engineering and Computer Science, 2017)
The mobile nodes can establish the route from source to destination when they want. In DSR routing protocols many loop hole are there, these loop holes can give arise to different type of active and passive attacks which are triggered by various inside and outside malicious nodes. Among all the type of attacks, black hole attack is the most common of attack which is possible in DSR protocol. Black hole attack is the denial of service attack. Many algorithms had been proposed to prevent this attack. In this paper, we are proposing modifications in traditional DSR protocol to prevent black hole attack.